Gender Gap under Pressure: Evidence from China's National College Entrance Examination - Cai, Xiqian; Lu, Yi; Pan, Jessica; Zhong, Songfa (The Review of Economics and Statistics, 2019)
We examine gender differences in the response to competitive pressure using data from the most competitive entrance exam—China's Gaokao. Compared to male students, females underperform on the competitive and high-stakes Gaokao, relative to their performance on the low-stakes mock examination. Moreover, women's performance suffers more than men's in response to negative performance shocks in an earlier exam on the same day. These effects are more pronounced for subgroups of students where the stakes matter more. Overall, these findings appear to be best explained by women's lower tolerance for pressure and weaker incentives to do well in high-stakes settings.